EXPLORING THE CONNECTION BETWEEN SECOND LANGUAGE VOCABULARY LEARNING STRATEGIES AND VOCABULARY KNOWLEDGE - Charkova, Denitza A.; Charkova, Krassimira (International Online Journal of Education and Teaching, 2018)
The present study sought to explore and identify vocabulary learning strategies that lead to the attainment of depth of vocabulary knowledge in a second language. For the purpose, 110 Bulgarian language learners of English took Qian and Schedl’s (2004) depth of vocabulary knowledge test and completed a related survey. After dividing the sample into a limited knowledge group and a superior knowledge group, the data were analyzed through discriminant function analysis which showed eight vocabulary learning strategies as significantly associated with the superior knowledge group. These strategies were named linguistically-driven strategies since they involve regular attention to linguistic features, including: paradigmatic associations (synonyms, antonyms), morphological structure (prefixes, roots, and suffixes), syntagmatic associations (collocations) and pronunciation. The results suggest that regular use of linguistically-driven vocabulary learning strategies helps build deep knowledge of second language vocabulary. Keywords: vocabulary learning strategies, depth of vocabulary knowledge, second language teaching, second language learning